Students’ Level of Self-Efficacy and Physical Fitness Performance: An Input to Instructional Material Development - Adamos, Danica (International Journal on Integrated Education, 2026)
This study aimed to determine the relationship between the level of self-efficacy and physical fitness performance of Bachelor of Science in Exercise and Sports Sciences (BSESS) students of Southern Luzon State University. Self-efficacy levels play an integral role in successfully accomplish certain tasks or goals. More so for achieving high levels of physical fitness performance, self-efficacy influences their motivation and confidence in engaging in activities geared towards improving physical fitness. A descriptive-correlational research design was used to assess the self-efficacy based on performance outcome, vicarious experience, verbal persuasion, and physiological feedback; and the levels of physical fitness performance in terms of skill and health-related physical fitness activities among BSESS students at Southern Luzon State University. A total of 89 college students were randomly selected as the respondents of the study. An adapted survey questionnaire was utilized to gather information on the respondents' self-efficacy levels and physical fitness performance. The respondents demonstrated high levels of self-efficacy in performance outcome, vicarious experience, and verbal persuasion nonetheless, in terms of physiological feedback, they showed a high level of self-efficacy. Finally, participants had very high levels of physical fitness performance both in skill and health-related physical fitness activities. The findings indicated a strong correlation between the physical fitness performance of the respondents and their level of self-efficacy. It is recommended to provide emphasis on enhancing the self-efficacy levels of students, especially in physiological feedback in order to further improve their physical fitness performance. Also, future researchers consider different research designs and methods in order to obtain generalizable and extensive results.